2013
DOI: 10.1111/his.12224
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem examination in the morbidly obese

Abstract: Postmortems in the morbidly obese represent a significant percentage of the total performed, but recognition of the contribution of obesity to death and of obesity-associated conditions is poor. Postmortems performed on the morbidly obese represent a distinct group with specific causes of death, and should be approached as such.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…This is consistent with the declaration of many publications that increased BMI is more hazardous for younger individuals . Our analyses aligned with previous reports that the most common causes of death were related to cardiovascular and respiratory disease when obesity was listed as a contributing factor in part II of the death certificate .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the declaration of many publications that increased BMI is more hazardous for younger individuals . Our analyses aligned with previous reports that the most common causes of death were related to cardiovascular and respiratory disease when obesity was listed as a contributing factor in part II of the death certificate .…”
Section: Discussionsupporting
confidence: 92%
“…The risk of sudden death due to an arrhythmia or unexpected cardiac death is nearly 40 times greater in the obese population as compared to the nonobese . Despite the known association between mortality and obesity, obesity is infrequently listed on the death certificate . Inconsistent certification of deaths due to, or contributed by, obesity vastly underestimates the effect obesity has on mortality.…”
mentioning
confidence: 99%
“…Instead, the majority of deaths were natural (N = 108), the leading causes of which were cardiac, pulmonary thromboembolism, and respiratory (32.6%, 12.5%, and 11.8% of all deaths, respectively). These results are similar to that of a study by Fryer et al, which found cardiac, respiratory, and pulmonary thromboembolism conditions to be the predominant causes of death in 42.6%, 19.8%, and 13.9% of their cases, respectively (16). Other studies have also shown that the prevalence of death due to cardiac causes is significantly higher in obese cohorts (14) and that obesity is not only a risk factor for fatal pulmonary thromboembolism (14,23,24), but that this becomes increasingly significant with rising BMI (15).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, histological or anatomical heterogeneity has the potential to confound study results (despite the best efforts of histopathologists and others to classify tumours accurately). In addition, the final cause of death in overweight people, as in lean subjects, is most often a cardiovascular or respiratory problem rather than GI disease …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the final cause of death in overweight people, as in lean subjects, is most often a cardiovascular or respiratory problem rather than GI disease. 90 Despite these considerations, there is no doubt that accumulation of body fat increases the risk of multiple non-neoplastic GI disorders and of oesophageal adenocarcinoma, CRC, and gallbladder cancer ( Table 1). One report estimated that 20% of gallbladder cancers and 11% of CRCs are 'attributable to obesity', and some experts have suggested even higher figures.…”
Section: Resultsmentioning
confidence: 99%